Komunikasi Dakwah Berbasis Digital dalam Mempertahankan Tradisi Randai di Kota Bukittinggi - Ramadhan, Ashri; Iswadi, Iswadi (BINA' AL-UMMAH, 2024)
This study aims to analyze the role of digital-based da'wah communication in preserving the Randai tradition in Bukittinggi City, West Sumatra, using a qualitative approach with literature analysis. Data were collected from various academic articles, books, and digital content discussing Randai and its integration with Islamic values through digital platforms. The analysis was conducted thematically to identify communication strategies, challenges, and the role of digital platforms in promoting cultural sustainability. The findings reveal that digital da'wah has been instrumental in reintroducing and preserving the Randai tradition, especially among the younger generation. Platforms such as YouTube and Instagram are often used to share Randai-related content, combining cultural narratives with Islamic teachings. Key strategies include the use of engaging visual content, and interactive discussions that highlight the philosophical and moral values embedded in Randai. However, the research also identified challenges such as limited internet access in rural areas, cultural resistance to modernization, and a lack of digital literacy among Randai practitioners, which hinder the wider adoption of digital proselytization for cultural preservation. The study concludes that digital proselytization provides a viable pathway to bridge the generation gap and encourage cultural preservation in the modern era. Effective collaboration between the cultural community and local government is essential to enhance the sustainability of the Randai tradition through innovative digital strategies.